MODULAR EDUCATION IN SECONDARY SCHOOL: ORIGINS, PROBLEMS, PROSPECTS (Pedagogy of Higher and Secondary Education, 2007)
On the basis of analysis of literary sources and front-rank pedagogical experience in the article historical bases and substantive theoretical provisions of the module teaching are shined at middle school Wide introduction of the module teaching in an educational process is examined as a prospect offurther development of ideas of the developing teaching.